2013
DOI: 10.1080/02640414.2012.735369
|View full text |Cite
|
Sign up to set email alerts
|

Do the effects of high intensity 40 km cycling upon left ventricular function and cardiac biomarker during recovery vary with time of day?

Abstract: Twelve healthy participants performed two identical high-intensity 40 km cycling trials (morning and evening) under controlled laboratory conditions. Echocardiograms and venous blood samples were collected before and after each exercise bout. Cardiac electro-mechanical-delay (cEMD) was measured as QRS-complex onset to peak systolic (S') and early diastolic (E') tissue velocities. Myocardial strain and strain rates were assessed in longitudinal, circumferential and radial planes at the left ventricular apex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Exercise was shown to significantly reduce RV longitudinal strain (LS) in two studies (1, 27) that involved >60 minutes of exercise, whereas RV LS was maintained in the study of Stewart et al(15), which involved <60 minutes of exercise. Longitudinal LV strain was significantly reduced in three studies (1,19,27), and unaffected following a 6 hour triathlon in the study of Leetmaa et al(23). The participants in this study were elite national-level triathletes and it is worth noting that the reported values were substantially higher than in all other studies (27.5% preexercise, 26.8% post).…”
mentioning
confidence: 49%
See 4 more Smart Citations
“…Exercise was shown to significantly reduce RV longitudinal strain (LS) in two studies (1, 27) that involved >60 minutes of exercise, whereas RV LS was maintained in the study of Stewart et al(15), which involved <60 minutes of exercise. Longitudinal LV strain was significantly reduced in three studies (1,19,27), and unaffected following a 6 hour triathlon in the study of Leetmaa et al(23). The participants in this study were elite national-level triathletes and it is worth noting that the reported values were substantially higher than in all other studies (27.5% preexercise, 26.8% post).…”
mentioning
confidence: 49%
“…Three studies (10,20,35) reported the previously obtained intra-individual CV of their echocardiographic measurements to demonstrate reliability. (19,20). It would appear from these findings that cycling exercise of up to minutes duration at low to moderate-intensities does not affect myocardial strain but high intensity cycling exercise of >60 minutes may negatively impact radial, circumferential and longitudinal strain.…”
Section: Blindingmentioning
confidence: 78%
See 3 more Smart Citations